Dictatorship, Democracy, and Transitional Justice in Global Legal History - Czeguhn, Ignacio; Thiessen, Jan (2023)
The anthology presents the lectures given on the symposium »From Dictatorship to democracy« at the House of the Wannsee Conference on 13–14 September 2021. The aim of the organizers was to show what problems existed during the transition from dictatorship to democracy in several countries around the world. They all enacted laws or other measures to ensure that fundamental rights and the rule of law would resist anti-democratic ideologies, anti-Semitism, racism, and war crimes in the future. However, the legal system and law in these countries themselves often had their origins in dictatorship. Thus, there were and are obvious and hidden anti-democratic continuities that influence law and the legal system up to the present. Scientifics and jurists from Italy, Japan, Poland, Spain, South Africa, and Germany examine these continuities in their contributions. / The anthology presents the lectures given on the symposium »From Dictatorship to democracy« at the House of the Wannsee Conference on 13–14 September 2021. The aim of the organizers was to show what problems existed during the transition from dictatorship to democracy in several countries around the world. They all enacted laws or other measures to ensure that fundamental rights and the rule of law would resist anti-democratic ideologies, anti-Semitism, racism, and war crimes in the future. However, the legal system and law in these countries themselves often had their origins in dictatorship. Thus, there were and are obvious and hidden anti-democratic continuities that influence law and the legal system up to the present. Scientifics and jurists from Italy, Japan, Poland, Spain, South Africa, and Germany examine these continuities in their contributions.